Effect of integrated nutrient management on growth, yield attributes and yield of green pea in humid subtropical climate of Indo-gangetic Plains - Aakash; M. K. Singh; Nilutpal Saikia; Lalita Bhayal; Divya Bhayal (Annals of Agricultural Research, 2023)
The field experiment was conducted during 2019-20 at Agriculture Research Farm, Banaras Hindu University, Varanasi, to study the effect of integrated nutrient management on growth attributes, yield attributes and yield of green pea. Eight integrated nutrient management (INM) treatments were formed, having different doses of phosphorus, nitrogen (through FYM), microbial consortia and waste decomposer. The experimental result showed that green pea performed better in terms of growth attributes (i.e. plant height, dry matter accumulation) and yield attributes (i.e. number of branches per plant, number of harvested pods) and green pod yield (84 and 39.7 q ha1 at first and second picking , respectively) when INM done in the following manner 60 kg P2 O5 ha-1 + 40 kg N ha-1 through farm yard manure + Microbial consortia (i.e. seed treatment with R. leguminosarum followed by soil application of PSB @ 1 litre ha-1) + two applications of waste decomposer @ 2500 litre ha-1 at sowing and pre-flowering stage.